Enhancing Data Recovery in RAID6: A Comparative Analysis of Row-Diagonal Parity Codes - Zhang Wenxu (ITM Web of Conferences)
RAID6 systems, known for their robust data protection and redundancy capabilities, encounter challenges in data recovery efficiency and computational complexity. This study investigates the efficacy of Row- Diagonal Parity (RDP) codes within RAID6 frameworks, emphasizing their ability to recover from dual disk failures. The exploration includes a detailed examination of the encoding and decoding processes of RDP codes, employing concrete examples to demonstrate these techniques. Comparative analysis highlights the computational advantages of RDP codes over traditional methods such as Reed-Solomon and EVENODD Codes. Findings reveal that RDP codes not only reduce computational complexity but also enhance data recovery speed significantly. Given these attributes, RDP codes offer a promising solution for large-scale data environments demanding high reliability and swift recovery. This approach markedly improves RAID6's functionality by optimizing recovery processes, thus supporting high-volume storage systems with stringent data integrity requirements. The potential for future enhancements in RAID6 data recovery through further research into hardware acceleration and artificial intelligence is also acknowledged, aiming to refine recovery times and efficiency in large-scale storage applications.